2023
DOI: 10.1371/journal.pone.0285272
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate is a population-level biomarker of cardiorespiratory fitness: The Fenland Study

Abstract: Introduction Few large studies have evaluated the relationship between resting heart rate (RHR) and cardiorespiratory fitness. Here we examine cross-sectional and longitudinal relationships between RHR and fitness, explore factors that influence these relationships, and demonstrate the utility of RHR for remote population monitoring. Methods In cross-sectional analyses (The UK Fenland Study: 5,722 women, 5,143 men, aged 29-65y), we measured RHR (beats per min, bpm) while seated, supine, and during sleep. Fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…Resting heart rate is inversely correlated with fitness in observational studies and decreases as a response to aerobic exercise training 2 , 22 25 . We hypothesised that resting heart rate could also be used as a viable proxy trait for fitness in a genetic framework and conducted several analyses to test this.…”
Section: Resultsmentioning
confidence: 99%
“…Resting heart rate is inversely correlated with fitness in observational studies and decreases as a response to aerobic exercise training 2 , 22 25 . We hypothesised that resting heart rate could also be used as a viable proxy trait for fitness in a genetic framework and conducted several analyses to test this.…”
Section: Resultsmentioning
confidence: 99%
“…The heart rate could reflect respiratory function, cardiac function and immune response. [24][25][26][27][28] Several studies showed that the heart rate could be exploited for the early identification of infections and respiratory diseases. 29,30 The vagus nerve was an important neuroimmunomodulator in the inflammatory pathway, and heart rate could reflect the function of the vagus nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The demographics of the participants are reported in Table 1 and include age (years), sex (female/male), body height (to the nearest 0.1 cm; barefoot), body mass (to the nearest 0.1 kg; barefoot and light clothing only), body mass index (calculated by dividing body mass by squared body height (kg•m −2 )), then following a 20 min seated posture, resting oxygen consumption (RVO 2 ; mL•kg −1 •min −1 ; standard temperature and dry gas at standard barometric pressure; assessed while sitting quietly on a chair for four minutes (as this time frame does not affect the accuracy of energy expenditure measurements [27])), and resting heart rate (beats per minute) as a proxy for physical fitness levels [28], except for participants who used heart rate controlling medication. The self-selected walking speed on a treadmill was referred to as preferred walking speed (km•h −1 ).…”
Section: Participant Characteristicsmentioning
confidence: 99%